The mediating effects of communication skills on stress management among higher education staff / Nur Liana Kori ... [et al.] - Kori, Nur Liana; Mat, Azmi; Saiful Bahry, Norliza; Mohd Ali, Ainunnazlee (Universiti Teknologi MARA, 2024)
This study examines the mediating of communication in a relationship between work practices, and organizational culture towards managing work stress. The current dynamics and increased competition in the services sector urge organizations to seek ways to improve performance, remain relevant in the face of technology and go through changes and innovation while keeping their employees healthy and productive. This paper surveyed 176 non-academicians across universities in Selangor. The data was analyzed using the Partial Least Squares Structural Equation (PLS-SEM), and the finding found that communication mediates the relationship between work practices and organizational culture toward stress management. The implication of this study highlights how essential communication skills are for improving organizational learning and employee performance. The study offers insightful information for improving staff productivity, well-being, and organizational development.